Mentat® ameliorates hypoxia-induced attention deficyt hyperactivity disorder like behavior in rats - Sindhura, Sai; Viswanatha, Gollapalle Lakshminarayanashastry; Jain, Chirag; Mallappa, Onkaramurthy; Azeemuddin, Mohammed Mukhram; Rafiq, Mohamed; Manjula, S.N. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. The objective of the study was to evaluate the effect of MentatR an herbal formulation in experimental models of hypoxia-induced attention deficit hyperactive disorder (ADHD) like behavior in rats. Material and methods. MentatR was evaluated at the dose of 100 and 200 mg/kg body weight. per oral., in two experimental models of hypoxia in Wistar rats. In the first model, after parturition, on a postnatal day 2 (PND-2), the pups were subjected to hypoxic exposure for 10 minutes to induce neonatal hypoxia. Pups were weaned from dams on PND-21 and subjected to drug treatments for 10 days. In the second model, phenytoin 150 mg/kg. b.wt. p.o. was administered orally to all pregnant animals throughout gestation to induce intrauterine hypoxia. Pups were subjected to assigned treatments after weaning. Behavioral and biochemical parameters relevant to ADHD were assessed. Results. In the positive control group, hypoxic exposure resulted in significant changes in cognitive and neurologic skills compared to normal control. Open field test, elevated plus maze test, and Acetylcholine esterase levels showed a significant increase in positive control compared to normal control. In treatment groups, there was a dose-dependent decrease in all the above parameters compared to positive control. Dopamine and Nor-epinephrine levels in brain homogenate were decreased in positive control which subsequently increased with MentatR treatment. Conclusion. MentatR showed a neuroprotective effect in different experimental models of ADHD. It may be recommended for the effective/preventive management of ADHD, especially associated with memory impairment and neurologic conditions.
Keywords: ADHD; herbal; Mentat®; neonatal hypoxia; neuroprotective